Health, Nutrition, and Hygiene Practices among Street Children at Raipur Railway Station: A Sociological Analysis of Vulnerabilities and Interventions (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Street children living in and around Raipur railway station face significant challenges in accessing basic health, nutrition, and hygiene resources, which contribute to persistent vulnerabilities. This paper is based on the study, conducted with a sample of 75 street children, explores their eating patterns, hygiene practices, and health outcomes, revealing critical insights into their lived realities. The analysis identifies a high prevalence of malnutrition, irregular and inadequate dietary habits, and poor personal hygiene, which collectively exacerbate their susceptibility to frequent illnesses and chronic health issues. Drawing on both quantitative data and qualitative narratives, the study highlights systemic barriers, such as lack of access to clean water, sanitation facilities, and nutritious food, as well as the absence of targeted health interventions. The findings underscore the urgent need for comprehensive policy frameworks and community-driven strategies to mitigate these challenges. Recommendations include implementing accessible feeding programs, providing mobile health services, and establishing hygiene awareness campaigns in collaboration with local stakeholders. By addressing the interconnected issues of health, nutrition, and hygiene, this research advocates for sustainable interventions that can significantly improve the well-being of street children and contribute to their long-term development.